2017
DOI: 10.1016/j.neo.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome DNA Methylation Profiling Identifies Epigenetic Signatures of Uterine Carcinosarcoma

Abstract: Uterine carcinosarcoma (UCS) is a form of endometrial cancer simultaneously exhibiting carcinomatous and sarcomatous elements, but the underlying molecular and epigenetic basis of this disease is poorly understood. We generated complete DNA methylomes for both the carcinomatous and the sarcomatous components of three UCS samples separated by laser capture microdissection and compared DNA methylomes of UCS with those of normal endometrium as well as methylomes derived from endometrioid carcinoma, serous endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The decrease in the epigenetic aging rate after 60 years is evident using both the list of 8823 age-DMPs and the shorter list including 687 probes mapping on 75 age-DMRs. In addition to the robustness emerging from confirming the results with two different approaches, the latter signature is defined using a region-centric approach 18 22,23 or in other cancer types (NEFM, KCNG3, PRDM14, FOXD3, CELSR3, HEYL) [24][25][26][27][28][29][30] , suggesting a role of these genes in liver homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the epigenetic aging rate after 60 years is evident using both the list of 8823 age-DMPs and the shorter list including 687 probes mapping on 75 age-DMRs. In addition to the robustness emerging from confirming the results with two different approaches, the latter signature is defined using a region-centric approach 18 22,23 or in other cancer types (NEFM, KCNG3, PRDM14, FOXD3, CELSR3, HEYL) [24][25][26][27][28][29][30] , suggesting a role of these genes in liver homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, as a major epigenetic modification, plays important roles in human diseases and aging ( 1 4 ), embryonic development of animals ( 5 8 ) as well as growth and development of plants ( 9 12 ). Recently, studies in human have found that DNA methylation biomarkers of aging are associated closely with mortality rates and incidence of cardio-metabolic disease ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, it is composed of an admixture of malignant epithelial and sarcomatous elements. The sarcoma component exhibits differentiation with histologic features of leiomyosarcoma, endometrial stromal sarcoma (ESS), or brosarcoma, or may resemble rhabdomyosarcoma, chondrosarcoma, osteosarcoma, or other heterologous sarcomas [25,26]. The low incidence and complex composition limit the researches.…”
Section: Discussionmentioning
confidence: 99%